2014
DOI: 10.1074/jbc.m114.562900
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol Increases Expression of the Pro-apoptotic BH3-only Protein NOXA through a Novel Mechanism Involving Phospholipase A2, Cytoplasmic Calcium, and Endoplasmic Reticulum Stress

Abstract: Background:The mechanism through which gossypol mediates anti-cancer activity is poorly understood. Results: Gossypol rapidly activates phospholipase A2, increases cytoplasmic calcium, endoplasmic reticulum stress, and NOXA, and sensitizes cells to apoptosis. Conclusion: Phospholipase A2 is a novel target of gossypol. Significance: This pathway can explain many reported activities of gossypol including sensitization to the BCL2 inhibitor,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 67 publications
1
45
0
Order By: Relevance
“…ATF3 can be induced by ER stress and is known to regulate Noxa gene transcription in collaboration with ATF4. 13,23 However, our data suggests that ATF3 is not required for Noxa transcript or protein induction in response to BNC105 as JNK inhibition completely prevented ATF3 induction but did not impact Noxa levels (Fig. 3).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…ATF3 can be induced by ER stress and is known to regulate Noxa gene transcription in collaboration with ATF4. 13,23 However, our data suggests that ATF3 is not required for Noxa transcript or protein induction in response to BNC105 as JNK inhibition completely prevented ATF3 induction but did not impact Noxa levels (Fig. 3).…”
Section: Discussionmentioning
confidence: 69%
“…However, Noxa induction has been reported to enhance apoptosis in CLL cells when used in combination with Bcl-2 targeting drugs ABT-737 and ABT-199. 13,30 The importance of Noxa induction was also suggested by results with normal leukocytes and CLL cells from Patient 81, neither of which induced Noxa or underwent acute apoptosis, despite the activation of JNK in both cases. Genomic analysis of Patient 81 revealed 2 large regions of chromosomal loss (located on 17p and 14q).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Treatment with gossypol may have various biochemical and molecular impacts on different cancers with specific biological behaviors. Gossypol is proposed to inhibit Bcl-2 and Bcl-XL and can also induce autophagic cell death as well as apoptosis through the Smac, p53, and caspase pathways [15][16][17]. Another study also showed that gossypol caused cancer cell cycle arrest at the G2/M or G0/G1 phases along with the down-regulation of Akt and phosphoAkt protein expression and the decreased the expression of cyclin D1, Cdk4, and phospho-Rb due to the up-regulation of TGF-beta1 expression and secretion [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These potential molecular targets related to the anticancer mechanisms of AT-101 include protein kinase C [37], cell cycle proteins Rb and cyclin D1 [19], NF-kB [24], ROSindependent mitochondrial pathway of apoptosis [11], Nor and induction of autophagy [18]. Recently, Soderquist et al [34] report that phospholipase A2 is a candidate of the molecular target responsible for the anticancer action of AT-101. In this study, we found that AT-101 may inhibit the Hh signaling pathway by potentially targeting Smo.…”
Section: Discussionmentioning
confidence: 98%